Implementasi Program Unggulan Tahfiz Qur’an dalam Penanaman Karakter Displin Siswa di Kelas Pesantren SMP Ma’arif NU 1 Cilongok Banyumas - Asdlori; Ernawati, Hesti (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This research is motivated by the decline in character that is rampant, many young people who are still in school have very minimal character, especially disciplined character. The current young generation finds it difficult to have disciplined traits. For that, in addition to the family environment, the school environment also plays an important role in instilling disciplined character in students. SMP Ma'arif NU 1 Cilongok is a school that has superior classes, namely Islamic boarding school classes. Islamic boarding school classes have a higher level of discipline compared to regular classes. This discipline is instilled through a series of activities contained in the superior taḥfīẓ Qur'an program. The main problem examined in this research is how to implement the superior taḥfīẓ Qur'an program in instilling students' disciplined character in the Islamic boarding school class of SMP Ma'arif NU 1 Cilongok. Previous research has mostly directly examined low levels of discipline in schools, but has been limited in studying schools that already have high levels of discipline. Therefore, this research aims to describe the implementation of the superior taḥfīẓ Qur'an program in Islamic boarding school classes, and analyze how the disciplinary character of students is cultivated in Islamic boarding school classes through the superior taḥfīẓ Qur'an program at SMP Ma'arif NU 1 Cilongok, Banyumas district. This research uses a qualitative descriptive method. Data was obtained through observation, interviews and documentation. The data analysis technique uses analysis techniques from Miles and Huberman. The research results show that the superior taḥfīẓ Qur'an program is packaged in the Islamic boarding school program, program implementation starts from planning, implementation and evaluation. Instilling the disciplined character of Islamic boarding school class students through taḥfīẓ Qur'an includes habituation, determining memorization targets, giving punishments & warnings, and giving awards.